An RNA modification enzyme directly senses reactive oxygen species for translational regulation in Enterococcus faecalis - Lee, Wei Lin (2023)
Bacteria possess elaborate systems to manage reactive oxygen and nitrogen species (ROS) arising from exposure to the mammalian immune system and environmental stresses. Here we report the discovery of an ROS-sensing RNA-modifying enzyme that regulates translation of stress-response proteins in the gut commensal and opportunistic pathogen Enterococcus faecalis. We analyze the tRNA epitranscriptome of E. faecalis in response to reactive oxygen species (ROS) or sublethal doses of ROS-inducing antibiotics and identify large decreases in N2-methyladenosine (m2A) in both 23 S ribosomal RNA and transfer RNA. This we determine to be due to ROS-mediated inactivation of the Fe-S cluster-containing methyltransferase, RlmN. Genetic knockout of RlmN gives rise to a proteome that mimics the oxidative stress response, with an increase in levels of superoxide dismutase and decrease in virulence proteins. While tRNA modifications were established to be dynamic for fine-tuning translation, here we report the discovery of a dynamically regulated, environmentally responsive rRNA modification. These studies lead to a model in which RlmN serves as a redox-sensitive molecular switch, directly relaying oxidative stress to modulating translation through the rRNA and the tRNA epitranscriptome, adding a different paradigm in which RNA modifications can directly regulate the proteome.